Analysis of marketing efficiency of processed sardine products of Lake Victoria: Case of Tanzania. Issue 1 (2nd January 2020) - Mkunda, Josephine Joseph; Lassen, Jesper; Chachage, Bukaza; Kusiluka, Lughano J.M.; Pasape, Liliane
Abstract : The paper tested the marketing efficiency of Lake Victoria processed sardines using structure-performance and efficient-structure hypotheses and the influence of socioeconomic characteristics on marketing efficiency. Primary data was collected using structured questionnaires from randomly selected 249 respondents. The conceptual framework showed the influence of market structure, performance and socioeconomic characteristics on marketing efficiency. Multiple regression and descriptive statistics were used to analyze the information. The Gini coefficients for traders and processors were 0.59 and 0.64; the Lorenz curves showed 80% of monthly income was accounted for by 50% of marketers indicating that the market was concentrated with high level of income and market shares inequalities. Empirical findings revealed that access to market information and formal business loans, selling price, net returns, and quantity traded significantly increase marketing efficiency. Marketing costs and margins significantly reduce marketing efficiency. Higher income and market share inequalities, poor access to business loans, markets and market information imply the market was imperfectly competitive and inefficient with greater likelihood of domination as economic and game theories suggests. The findings call for collective marketing in order to reduce marketing cost, increase the quantity traded and fishers' bargaining power in order to increase their net returns.